The most massive galaxies in clusters are already fully grown at z ∼ 0.5 - Oldham, L; Houghton, R; Davies, R (Oxford University Press, 2016)
By constructing scaling relations for galaxies in the massive cluster MACSJ0717.5 at z = 0.545 and comparing with those of Coma, we model the luminosity evolution of the stellar populations and the structural evolution of the galaxies. We calculate magnitudes, surface brightnesses and effective radii using Hubble Space Telescope (HST)/ACS images and velocity dispersions using Gemini/GMOS spectra, and present a catalogue of our measurements for 17 galaxies. We also generate photometric catalogues for ∼3000 galaxies from the HST imaging. With these, we construct the colour–magnitude relation, the Fundamental Plane, the mass-to-light versus mass relation, the mass–size relation and the mass–velocity dispersion relation for both clusters. We present a new, coherent way of modelling these scaling relations simultaneously using a simple physical model in order to infer the evolution in luminosity, size and velocity dispersion as a function of redshift, and show that the data can be fully accounted for with this model. We find that (a) the evolution in size and velocity dispersion undergone by these galaxies between z ∼ 0.5 and z ∼ 0 is mild, with Re(z) ∼ (1 + z)^−0.40 ± 0.32 and σ(z) ∼ (1 + z)^0.09 ± 0.27, and (b) the stellar populations are old, ∼10 Gyr, with a ∼3 Gyr dispersion in age, and are consistent with evolving purely passively since z ∼ 0.5 with ΔlogM/LB=−0.55+0.15−0.07z. The implication is that these galaxies formed their stars early and subsequently grew dissipationlessly so as to have their mass already in place by z ∼ 0.5, and suggests a dominant role for dry mergers, which may have accelerated the growth in these high-density cluster environments.